Occupational Success Satisfaction: An Empirical Study of Selected Professionals in India - Bala, Kiron; Sandhu , Amandeep (Gyan Management Journal, 2013)
Within the vast literature on the antecedents of occupational or career success, the success criterior. has9e11eral/y been operationalized in a rather deficient manner. This paper illustrates that contextua: and individual factors are likely to be associated with the relative salience of objective and subjective criteria of career success. This study maps out how future research can be more sensitive to how people actua fly do conceptualize and evaluate their own occupationa I or career success.
Keywords: occupational; career success; criterior